Relationships Marketing, as a New Direction of a Marketing Theory - Kėdaitienė, Angelė (Ekonomika, 1999)
The interest in relationships marketing has grown in recent years and is now beginning to take center stage in marketing thought and research. Relationships marketing covers the whole spectrum of marketing’s sub-disciplines and also integrates concepts and theoretical paradigms from several social science disciplines, including economics, sociology, psychology and political science. The full potential of relationships marketing has implications for organizational changes and for creating superior marketing value. Several indications suggest that it will have a broad appeal and would encourage widespread academic inquiry.The aim of this article would be to present various points of view to relationships marketing and highlight concepts which, according to authors point of view, carry out the highest level of relation-ships marketing correlation with classical marketing theory and which are the most important to present practical marketing activity, to marketing management and marketing research.